Kesejahteraan Anak di Era Overstimulasi Digital: Kajian Literatur tentang Dampak Konten Cepat terhadap Regulasi Emosi Anak Usia Dini - Rizka Aulia Nursya’bani; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
The digital era has revolutionized stimulation patterns in early childhood due to massive exposure to short-duration digital content that is rapid and intensive. This overstimulasi phenomenon is suspected as the primary etiological factor in the deficiency of emotional response regulation in children. This study aims to analyze the implications of digital content overstimulasi on the emotional regulation capabilities of early childhood through a comprehensive literature review. The applied methodology is a library study, involving the analysis of 20 reputable national journal articles published within the 2021–2025 period, accessed from the Google Scholar, Sinta, and Garuda databases. Substantial findings indicate that excessive exposure to high-speed content (high screen time) induces non-physiological dopamine release, resulting in a decreased frustration tolerance threshold, increased tantrum incidence, and degradation of attention span. Digital content overstimulasi inhibits the maturation of the prefrontal cortex as the center of emotional regulation. Children's psychological well-being in the digital era is highly conditional on the moderation of digital device usage. A synergy between parental supervision (mediated monitoring) and exposure duration limitations is required to maintain the stability of children's emotional regulation